Spring in Action, 4th Ed, Video Edition - Walls, Craig (Manning Publications, 2018)
"The classic, remastered and full of awesomeness." Mario Arias, Cake Solutions Ltd Spring in Action, Fourth Edition is a hands-on guide to the Spring Framework, updated for version 4. It covers its latest features, tools, and practices including Spring MVC, REST, Security, Web Flow, and more. You'll move between short snippets and an ongoing example as you learn to build simple and efficient J2EE applications. Author Craig Walls has a special knack for crisp and entertaining examples that zoom in on the features and techniques you really need. Designed in 2003 as a lighter approach to J2EE development, Spring Framework has since become a standard choice for building enterprise applications and required knowledge for Java developers. Spring 4 provides full Java 8 integration along with key upgrades like new annotations for the IoC container, improvements to Spring Expression Language, and much-needed support for REST. Whether you're just discovering Spring or you want to absorb the new features, there's no better way to master Spring than with this book. Inside: Updated for Spring 4 Spring Data for NoSQL Simplifying configuration with annotations and definition profiles Working with RESTful resources Nearly 100,000 developers have used the book version to learn Spring! Spring in Action requires a working knowledge of Java. Craig Walls is a software developer at Pivotal. He's a popular author and a frequent speaker at user groups and conferences. Craig lives in Cross Roads, Texas. Informative, accurate and insightful! Jeelani Shaik, D3Banking.com After ten years, this is still the clearest and most comprehensive introduction to the core concepts of the Spring platform. James Wright, Sword-Apak NARRATED BY MARK THOMAS.